2015
DOI: 10.1371/journal.pone.0118584
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Family Planning Advice on Unmet Need and Contraceptive Use among Currently Married Women in Uttar Pradesh, India

Abstract: BackgroundCounseling/advice is one of the key interventions to promote family planning (FP) in developing countries, including India. It helps to improve the quality of care and reduce maternal deaths. This paper investigates the continuity of maternal health (MH) service utilization from antenatal care to post-natal care and the impact this service utilization has on contraceptive use and on meeting the demand for family planning among currently married women in rural Uttar Pradesh, India.Methods and Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 53 publications
5
34
0
1
Order By: Relevance
“…In our study, the longer time-to-contraceptive use observed among women who attended 1-3 ANC visits compared with those who attended the recommended four or more visits supports this finding as noted elsewhere [51]. Thus, strengthening the integration of family planning into ANC services [23,26,52,53] would certainly go a long way in promoting modern contraceptive use, particularly during the postpartum period.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In our study, the longer time-to-contraceptive use observed among women who attended 1-3 ANC visits compared with those who attended the recommended four or more visits supports this finding as noted elsewhere [51]. Thus, strengthening the integration of family planning into ANC services [23,26,52,53] would certainly go a long way in promoting modern contraceptive use, particularly during the postpartum period.…”
Section: Discussionsupporting
confidence: 82%
“…In a recent study on family planning advice and contraceptive use, Yadav and Dhillon [26] show that use of critical maternal health services (ANC, institutional delivery, and postnatal care) encourages subsequent contraceptive use. In Tanzania, findings that showed counseling had an influence on the intention to use contraception [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The supply-side factors including inaccessibility of comprehensive contraceptive services and poor information dissemination are among the factors related to young women unmet need for contraception. [15][16][17] Limited knowledge of contraceptive methods was also found to have a significant effect on the unmet need for contraception. 18,19 Demographic and economic characteristics including women's age, age of marriage, educational status, residence of living, duration after marriage, and wealth status were also associated with young married women unmet need for contraception in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…We include whether the child was breastfed for 6 months or more as a favorable event. Adverse outcomes include the prevalence of anemia in children and pregnant women; the prevalence of vision 14 A number of studies have demonstrated that family planning visits and counseling are associated with the increased use of modern contraceptive methods, thereby supporting our use of the reported prevalence of modern contraception use as a proxy measure for family planning visits (Ahmed and Mosley 2002, Barber 2007, Borges, OlaOlorun et al 2015, Yadav and Dhillon 2015.…”
Section: Dependent Variablesmentioning
confidence: 91%